Facile green synthesis of boroncarbonitride using orange peel; Its application in high-performance supercapacitors and detection of levodopa in real samples. (September 2020) - Raghu, M.S.; Parashuram, L.; Kumar, K. Yogesh; Prasanna, B.P.; Rao, Srilatha; Krishnaiah, Prakash; Prashanth, K.N.; Kumar, C.B. Pradeep; Alrobei, H.
Graphical abstract: Abstract: From the past few years 2D materials have emerged as a choice of research materials in the field of electrochemistry. Boroncarbonitride (BCN) is one such 2D material synthesized by facile, novel, one-step pyrolysis method using activated carbon obtained by orange peel extract as a source of carbon. Synthesized BCN has been characterized and used as electrode material for supercapacitor applications using cyclic voltammetry (CV), chronopotentiometry (CP) and Electrochemical Impedence Spectroscopy (EIS) techniques. BCN has also been utilized for sensitive detection of levodopa (L-DOPA).The specific capacitance of BCN as an electrode material was 391 F g −1 at a scan rate of 5 mVs −1 by using CV technique and achieved a capacitance of 209 F g −1 at a current density of 2.5 Ag −1 as calculated by CP. Levodopa detection was also carried out using BCN modified carbon paste electrode, it shows a linear range of current response over 0.2–160 μM of L-DOPA concentrations and having a limit of detection of 0.14 μM. Differential pulse votammetry (DPV) response for L-DOPA was very stable even after 2 weeks and observed 92 % of the initial peak current response. L-DOPA detection was also been carried out in spiked human urine samples and the percentage recovery was observed in the range of 98.6 ± 2.1–102.06 ± 2.9 %. From the obtained results, it is clear that BCN serve as a good electrode material in supercapacitors and sensitive electrocatalyst for the analysis of L-DOPA in real samples.